2023
DOI: 10.1002/ajb2.16147
|View full text |Cite
|
Sign up to set email alerts
|

Do Silene species with exposed stigmas tolerate interference by heterospecific pollen?

Abstract: Premise: Co-flowering species that have not evolved an avoidance mechanism may have tolerance to heterospecific pollen (HP) deposition as an adaptive strategy to minimize any deleterious effects of HP transfer, but empirical evidence for the tolerance hypothesis remains scarce. Methods: To estimate the potential effects of heterospecific pollen deposition (HPD) on female reproductive success, we counted conspecific (CP) and HP pollen grains deposited on stigmas and assessed subsequent seed set of both open-and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 45 publications
0
13
0
1
Order By: Relevance
“…For example, several studies included in this special issue estimate trait–performance relationships by relating floral phenotype to pollen placement or deposition in the field (e.g., Capó et al, 2023; Dellinger et al, 2023; Pérez‐Barrales and Armbruster, 2023; Rodríguez‐Otero et al, 2023). The corresponding performance–fitness relationship can be studied through experimental manipulation of pollen loads in the field or greenhouse to infer pollen‐to‐seed curves or the influence of heterospecific pollen deposition on the relationship between conspecific pollen deposition and seed set (e.g., Hao et al, 2023; Moreira‐Hernández et al, 2023; Pérez‐Barrales and Armbruster, 2023). While these kinds of results are increasingly available, it is still rare to see them combined into a complete fitness function of the kind illustrated in Figure 1, and we hope that this special issue will inspire further work along this line.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, several studies included in this special issue estimate trait–performance relationships by relating floral phenotype to pollen placement or deposition in the field (e.g., Capó et al, 2023; Dellinger et al, 2023; Pérez‐Barrales and Armbruster, 2023; Rodríguez‐Otero et al, 2023). The corresponding performance–fitness relationship can be studied through experimental manipulation of pollen loads in the field or greenhouse to infer pollen‐to‐seed curves or the influence of heterospecific pollen deposition on the relationship between conspecific pollen deposition and seed set (e.g., Hao et al, 2023; Moreira‐Hernández et al, 2023; Pérez‐Barrales and Armbruster, 2023). While these kinds of results are increasingly available, it is still rare to see them combined into a complete fitness function of the kind illustrated in Figure 1, and we hope that this special issue will inspire further work along this line.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, however, if pollinators also tend to deposit more conspecific pollen when they deposit more heterospecific pollen, increased heterospecific pollen deposition may actually correspond to greater seed set (e.g., Lopes et al, 2021), especially if the recipient species has evolved a degree of tolerance to heterospecific pollen. For example, in this issue, Hao et al (2023) studied patterns and consequences of heterospecific pollen deposition onto stigmas in three Silene species and found that stigmas receiving more heterospecific pollen also tended to receive more conspecific pollen and that hand-pollination with mixtures of conspecific and heterospecific pollen did not usually reduce seed production compared to those with only conspecific pollen. Such tolerance likely evolves in response to natural exposure to heterospecific pollen.…”
Section: Heterospecific Pollen Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the L. suffruticosum locality where L. tenue was used as pollen donor is a single‐species locality; these plants experienced a stronger reduction of conspecific‐pollen performance than did plants from coflowering localities, which were pollinated with L. narbonense and L. viscosum pollen (see Material and Methods, Appendix S2). Variation in the tolerance to interspecific pollen based on a previous history of pollen exposure has been identified as an adaptive mechanism to reduce reproductive costs (Grant, 1966; Arceo‐Gómez et al, 2016; Fang et al, 2019; Moreira‐Hernández et al, 2019; Streher et al, 2020; Hao et al, 2023 [in this issue]).…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of pollen–pistil incompatibilities underlying post‐pollination isolation mechanisms also require evolutionary time, and thus efficiency of these barriers is expected to increase with phylogenetic distance between the interacting species (Ashman and Arceo‐Gómez, 2013; Moreira‐Hernández and Muchhala, 2019; Streher et al 2020). However, tolerance to heterospecific pollen deposition conferred by post‐pollination barriers among congeneric species has been observed in a few cases (e.g., Clarkia , Arceo‐Gómez et al, 2016; Burmeistera , Moreira‐Hernández et al, 2019; Silene , Hao et al, 2023 [in this issue]), suggesting that it might evolve more rapidly under some circumstances. In particular, cases where such barriers are present in sympatry but are absent between allopatric populations (e.g., Kay and Schemske, 2008; Arceo‐Gómez et al, 2016) suggest that pollen transfer dynamics in sympatry might favor the evolution of post‐pollination barriers to limit reproductive interference or prevent hybridization (Moreira‐Hernández and Muchhala, 2019).…”
mentioning
confidence: 99%